Distinction criteria for fiscal torts - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The author considers the issue of differentiation of fiscal torts. The author pays particular attention to the criterion of statutory threshold and an act of lesser significance. During the detailed analysis of both definitions, the author indicates deficits and drawbacks in terms of their statutory regulations. The critical comments allow the author to formulate proposals of changes in this normative area.
Keywords: wykroczenie skarbowe; przestępstwo skarbowe; akt o mniejszym znaczeniu; próg ustawowy